Rancang Bangun Automatic Contactless Thermometer Berbasis Arduino Uno - Cahyo Putro; Fitri Anindyasari; Septi Aprilia; Ipin Prasojo (STIKes Ibnu Sina Ajibarang, 2024)
The Covid-19 virus emerged in late 2019 in Wuhan, China, rapidly spreading to over 190 countries worldwide. Governments implemented various measures, including body temperature checks as an initial step in detecting Covid-19 symptoms. However, manual body temperature measurement using a thermogun has limitations due to direct contact. Therefore, this research develops an automatic, contactless body temperature monitoring system based on Arduino Uno to improve efficiency and reduce physical contact. The system uses an HC-SR04 ultrasonic sensor as a distance limiter for temperature measurement, an MLX-90614 infrared temperature sensor for detecting body temperature, and an Arduino Uno to process data displayed on an LCD in degrees Celsius, with a buzzer as a notification indicator. The test results show that this system achieves a body temperature measurement accuracy of 99.53%, producing results close to the reference device when the object and sensor are within a 1–5 cm range and aligned in a parallel position.